Manufacturing process of ultralow-temperature XM16 precipitation type martensitic stainless steel

Through three-stage heating and solid solution aging process, the problems of tissue refinement and low-temperature performance improvement of XM16 stainless steel during forging are solved, and the high strength and toughness of the material at low temperatures are achieved.

CN119194014APending Publication Date: 2024-12-27JIANGYIN ZENKUNG FORGING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411530196.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

During the forging process, XM16 stainless steel has increased difficulty in forging due to high strength and high toughness requirements. There are too many coarse and heterogeneous crystals in the alloy structure, and the toughness decreases at low temperatures, and the brittle phase aggregation causes the material to break easily at low temperatures.

Method used

The three-stage heating and solid solution aging process are adopted to gradually soften the blank, release internal gravity, and refine the grains to form a uniform martensite structure, reduce the brittle transition temperature, reduce dislocation and phase interface, and improve the low-temperature performance.

Benefits of technology

The low-temperature strength and toughness of XM16 stainless steel are improved, the risk of brittle fracture is reduced, the mechanical properties and processing properties of the alloy are optimized, and the material maintains high yield strength and tensile strength at low temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194014A_ABST
    Figure CN119194014A_ABST
Patent Text Reader

Abstract

The invention relates to a manufacturing process of ultralow-temperature XM16 precipitation type martensitic stainless steel. The manufacturing process comprises the following steps that S1, raw materials are prepared, wherein C is smaller than or equal to 0.03%; less than or equal to 0.50% of Si; 0.50% or less of Mn; less than or equal to 0.015% of P; less than or equal to 0.015% of S; the alloy comprises the following components in percentage by weight: 8.0 to 9.5 percent of Ni, 11.5 to 12.5 percent of Cr, 2.0 to 2.5 percent of Cu, 1.0 to 1.4 percent of Ti and 0.15 to 0.50 percent of Mo; step S2, forging deformation: step 1, heating a blank to 550 + / -20 DEG C; 2, the blank is heated to 850 + / -20 DEG C; 3, the blank is heated to 1170 + / -10 DEG C; 4, deformation is conducted, and the finish forging temperature of the forge piece is controlled to be 830 + / -15 DEG C; step S3, solid solution: step 1, first-stage solid solution is carried out, and the solid solution temperature range is 880 + / -10 DEG C; 2, second-stage solid solution, wherein the solid solution temperature range is 880 + / -10 DEG C; and S4, aging is conducted, and the aging temperature range is 460-560 DEG C. The method has the beneficial effects that forging defects are eliminated, coarse grains and mixed grains in the structure are reduced, the impact toughness index of the precipitation type martensitic stainless steel at the ultralow temperature is improved through fine grain strengthening, and the forging quality is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy forging manufacturing, and in particular to a manufacturing process of ultra-low temperature XM16 precipitation type martensitic stainless steel. Background Art

[0002] Martensitic stainless steel is a type of metal material based on iron, nickel and cobalt that can work for a long time at high temperatures above 600°C and under certain stress. XM16 stainless steel is a type of martensitic stainless steel, also known as S45500 or Custom455. It is a stainless steel alloy with comprehensive properties such as high strength, high toughness, high corrosion resistance, high oxidation resistance, excellent formability and weldability. XM16 stainless steel has been widely used in many fields due to its excellent performance. It is often used to manufacture parts that require extremely high strength and corrosion resistance.

[0003] The metallographic structure of XM16 stainless steel is mainly composed of martensite matrix and some residual phases, such as ferrite and nitride, etc. It has high strength and hardness, which requires greater forging force and plastic deformation ability during forging. With the increase of plastic deformation, work hardening phenomenon will occur, which will lead to further increase of forging force, and comprehensively increase the difficulty of forging. The alloy structure cannot be fully deformed, resulting in too many coarse grains and miscellaneous grains in the alloy structure, resulting in a large number of dislocations and phase interfaces inside XM16 stainless steel. These defects are more likely to become the source of crack initiation and expansion at low temperature. At the same time, there are a large number of residual brittle phases, such as ferrite and nitride. These brittle phases gather in large quantities at the grain boundaries, which will lead to a decrease in the toughness of the material at low temperature and affect the low temperature performance of XM16 stainless steel.

[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0005] Aiming at the deficiencies of the prior art, the present invention is disclosed.

[0006] The technical solution adopted by the present invention is as follows:

[0007] A manufacturing process of ultra-low temperature XM16 precipitation type martensitic stainless steel comprises the following steps:

[0008] Step S1, raw material preparation, XM16 precipitation type martensitic stainless steel includes the following components by weight percentage: C≤0.03%; Si≤0.50%; Mn≤0.50%; P≤0.015%; S≤0.015%; Ni: 8.0-9.5%, Cr: 11.5-12.5%, Cu: 2.0-2.5%, Ti: 1.0-1.4%, Mo: 0.15-0.50%; the balance is Fe;

[0009] Step S2, forging deformation, includes the following steps:

[0010] Step 1: First stage forging heating: the billet is heated to 550±20℃ and kept warm;

[0011] Step 2: The second stage of forging heating: the billet is heated to 850±20℃ and kept warm;

[0012] Step 3: The third stage of forging heating: the billet is heated to 1170±10℃ and kept warm;

[0013] Step 4: Deformation: The final forging temperature of the forging is controlled at 830±15℃. After forging, the forging is cooled;

[0014] Step S3, solid solution, includes the following steps:

[0015] Step 1: first stage solid solution, the solid solution temperature range of the forging is 880±10℃, and then the forging is cooled;

[0016] Step 2, second stage solid solution, the solid solution temperature range of the forging is 880±10℃, and then the forging is cooled;

[0017] Step S4: Aging. The aging temperature of the forging is in the range of 460 to 560°C.

[0018] Furthermore, in step 1 of step S2, the heating time rate of the forging is ≤60°C / h, and the holding time of the forging is determined according to the thickness of the forging, specifically 2-2.5h / 100mm.

[0019] Furthermore, in step 2 of step S2, the heating time rate of the forging is ≤60°C / h, and the holding time of the forging is determined according to the thickness of the forging, specifically 2-2.5h / 100mm.

[0020] Furthermore, in step 3 of step S2, the heating time rate of the forging is ≤60°C / h, and the holding time of the forging is determined according to the thickness of the forging, specifically 2.5-3h / 100mm.

[0021] Furthermore, in step 4 of step S2, the forging is cooled by water.

[0022] Furthermore, in step 1 of step S3, the temperature of the forging entering the furnace is less than or equal to 240° C., and the solution heat preservation time of the forging is in the range of 3 to 5 hours.

[0023] Furthermore, in step 2 of step S3, the temperature of the forging entering the furnace is less than or equal to 240° C., and the solution heat preservation time of the forging is in the range of 3 to 5 hours.

[0024] Further, in step S3, the forging is water-cooled after the first stage of solid solution treatment is completed, and the forging is water-cooled after the second stage of solid solution treatment is completed.

[0025] Furthermore, in step S4, the aging holding time of the forging is in the range of 2 to 3 hours.

[0026] Furthermore, in step S4, the forging is air-cooled to room temperature after aging.

[0027] The beneficial effects of the present invention are as follows:

[0028] 1. Increase the Ni content in the XM16 component. Nickel helps to reduce the brittle transition temperature of martensitic stainless steel by refining grains and promoting the precipitation of beneficial phases (such as ε-carbide). The material is not prone to brittle fracture when subjected to impact or stress, and the strength and toughness at low temperatures are improved; Cu and chromium are one of the important elements for forming martensitic structure. An appropriate amount of chromium content helps to obtain an ideal martensitic structure during heat treatment. Chromium precipitates with other alloying elements to form fine strengthening phases, reduce coarse grains and miscellaneous grains, and avoid excessive dislocations and phase interfaces. Increasing the chromium content also helps to reduce the brittle transition temperature of stainless steel; Ti precipitates fine strengthening phases such as TiC and TiN during aging treatment. The strengthening phases work together with the martensitic matrix to make the material It can still maintain a high yield strength and tensile strength at low temperatures. The precipitated phase of Ti can also serve as an obstacle to crack propagation, slowing down or preventing the rapid propagation of cracks at low temperatures, thereby improving the material's fracture resistance. Mo promotes the formation of a more uniform and fine microstructure of stainless steel during heat treatment, optimizes the dispersion distribution of reversed austenite, and promotes grain refinement. After solid solution and aging, molybdenum precipitates together with other alloying elements to form a fine strengthening phase, which can further improve the material's low-temperature strength and toughness. Cu can cooperate with other elements in aging treatment to precipitate a fine strengthening phase, and as one of the precipitation hardening elements, the strengthening phase works together with the martensitic matrix to help refine the microstructure of stainless steel and improve the material's strength and hardness.

[0029] 2. Before forging, the three-stage heating and heat preservation gradually softens the blank and releases the internal gravity, which is beneficial to the subsequent forging deformation, can refine the alloy grains, improve its organizational structure, improve the alloy's mechanical properties and processing properties, and the material completes full deformation, eliminates some internal defects such as pores and shrinkage, and improves the comprehensive mechanical properties of the forging.

[0030] 3. In the solution treatment, alloy elements such as chromium, nickel, molybdenum, etc. have been fully dissolved into the matrix (such as iron) to form a uniform solid solution structure, further reducing the coarse crystals and miscellaneous crystals in the alloy structure and increasing the grain size of the alloy. (To be supplemented: curve chart, two types, 1 strength index at the same temperature and different holding time; 2 strength index at the same holding time and different temperatures)

[0031] 4. After aging, a small amount of second phase is precipitated from the matrix. The second phase particles can hinder the movement of dislocations, and finally obtain a fine and uniform martensite structure, thereby improving the strength and hardness of the alloy. (To be supplemented: curve chart, two types, 1 impact index at the same temperature and different holding time; 2 impact index at the same holding time and different temperature) BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Schematic diagram of the manufacturing process steps of ultra-low temperature XM16 precipitation martensitic stainless steel.

[0033] Figure 2 This is the metallographic diagram of inclusions in Example 1.

[0034] Figure 3 This is the grain size metallographic diagram of Example 1.

[0035] Figure 4 This is the microstructure diagram of Example 1.

[0036] Figure 5 This is the metallographic diagram of inclusions in Example 2.

[0037] Figure 6 This is the grain size metallographic diagram of Example 2.

[0038] Figure 7 This is the microstructure diagram of Example 2.

[0039] Figure 8 This is the metallographic diagram of inclusions in Example 3.

[0040] Fig. 9 This is the grain size metallographic diagram of Example 3.

[0041] Fig.10 This is the microstructure diagram of Example 3.

[0042] Fig.11 This is the yield strength curve of samples at different temperatures with the holding time kept constant for 1h after solution treatment.

[0043] Fig.12 This is the yield strength curve of the sample kept at 880℃ for different time after solid solution.

[0044] Fig.13This is a curve of the average impact energy of the sample at -196°C under different aging temperatures after aging.

[0045] Fig.14 This is a curve of the average impact energy of the sample at -196℃ with the aging temperature controlled at 510℃ and different holding times after aging. DETAILED DESCRIPTION

[0046] The specific implementation of the present invention will be described below in conjunction with the accompanying drawings.

[0047] Embodiment 1:

[0048] A manufacturing process for ultra-low temperature XM16 precipitation type martensitic stainless steel, such as Figure 1 As shown, the following steps are included:

[0049] Step S1, raw material preparation:

[0050] The raw materials include elements counted by weight percentage, C 0.01%, Si 0.36%, Mn 0.36%, P 0.015%, S 0.002%, Cr 11.48%, Ni 9.38%, Mo 0.47%, Ti 1.24%, Cu 2.46%, Ta and Nb 0.26% in total, and the balance is iron.

[0051] Smelting method: vacuum smelting + vacuum consumables. During vacuum smelting and vacuum consumables, since the entire smelting process is carried out under vacuum or near-vacuum conditions, the contamination of molten steel by impurities such as air and oxygen is effectively avoided, and the formation of inclusions such as oxides and sulfides is reduced, thereby significantly improving the purity and organizational stability of the molten steel. In addition, the alloy raw materials can be more evenly dissolved in the molten steel, making the distribution of various elements more uniform, greatly reducing the occurrence of component segregation.

[0052] Step S2, forging deformation, includes the following steps:

[0053] Step 1: The first stage of forging heating: the forging is heated with the furnace, the heating rate of the forging is ≤60℃ / h, the billet is heated to 530℃ and kept warm, the holding time of the forging is determined according to the thickness of the forging, specifically 2-2.5h / 100mm.

[0054] Step 2: The second stage of forging heating: the forging is heated with the furnace, the heating time of the forging is ≤60℃ / h, the billet is heated to 830℃ and kept warm, the heating time of the forging is ≤60℃ / h, and the holding time of the forging is determined according to the thickness of the forging, specifically 2-2.5h / 100mm.

[0055] Step 3, the third stage of forging heating, the forging is heated with the furnace, the heating time of the forging is ≤60℃ / h, the billet is heated to 1160℃ and kept warm, the holding time of the forging is determined according to the thickness of the forging, specifically 2.5-3h / 100mm.

[0056] Step 4, forging, forging blank size φ560mm*2300mm, upset to H=1500mm, flatten after upsetting, draw to 650mm*1500mm, return to the furnace for insulation>4h, the blank is taken out of the furnace and upset to a height of 550mm Vertically press the outer diameter to 700mm, turn 90° to press the outer diameter to 700mm, turn 90° to press the outer diameter to 500mm, and then upset to a height of 550mm, square and lengthen, finish forming, and lightly chamfer the edges and corners. After forging is completed, the forging is heated to 815℃ in the furnace, kept warm for 2 to 3 hours, and finally water-cooled.

[0057] Step S3, solid solution, includes the following steps:

[0058] Step 1: The first stage is solid solution. The forging temperature into the furnace is 240°C, the solid solution temperature of the forging is 870°C, the solid solution holding time of the forging is 3h, and then the forging is water-cooled to room temperature.

[0059] Step 2, the second stage of solid solution, the forging furnace temperature is 180℃, the forging solid solution temperature is 870℃, the forging solid solution holding time is 3h, and then the forging is water cooled to room temperature.

[0060] Step S4, aging, includes the following steps:

[0061] The forgings’ entry temperature into the furnace is 140°C, the forgings’ aging temperature is 460°C, the forgings’ aging holding time is 2h, and the forgings are air-cooled to room temperature after being taken out of the furnace.

[0062] Finally, the forgings are sampled and comprehensively tested. After the quality is qualified, the forgings are rough-turned and delivered.

[0063] Forging inspection:

[0064] Comprehensive mechanical testing:

[0065] The forgings were subjected to tensile tests and impact tests, and the results are shown in Table 1.

[0066]

[0067] Table 1

[0068] At ultra-low temperatures (-196°C), the three-dimensional impact energy of the material meets the standard requirements, indicating that the material still has good strength and toughness at ultra-low temperatures.

[0069] Non-metallic inclusion detection:

[0070] Detection method: Ⅲ6GOST1778-70.

[0071] Test results: Figure 2 shown.

[0072] Grain size detection:

[0073] Test method: ASTME112-2017.

[0074] Magnification: 100x.

[0075] Acceptance index: Grain size ≥ level 6.

[0076] Test results: Figure 3 As shown, the grain size is level 7.

[0077] Tissue testing:

[0078] Test method: GB / T13298-2015.

[0079] Magnification: 100x.

[0080] Acceptance criteria: Ferrite is not allowed.

[0081] Test results: Figure 4 As shown, the structure is martensite, and no ferrite is seen.

[0082] Embodiment 2:

[0083] A manufacturing process for ultra-low temperature XM16 precipitation type martensitic stainless steel, such as Figure 1 As shown, the following steps are included:

[0084] Step S1, raw material preparation:

[0085] The raw materials include elements counted by weight percentage, C 0.016%, Si 0.33%, Mn 0.35%, P 0.014%, S 0.003%, Cr 11.71%, Ni 9.36%, Mo 0.44%, Ti 1.19%, Cu 2.42%, Ta and Nb 0.25% in total, and the balance is iron.

[0086] Smelting method: vacuum smelting + vacuum consumables. During vacuum smelting and vacuum consumables, since the entire smelting process is carried out under vacuum or near-vacuum conditions, the contamination of molten steel by impurities such as air and oxygen is effectively avoided, and the formation of inclusions such as oxides and sulfides is reduced, thereby significantly improving the purity and organizational stability of the molten steel. In addition, the alloy raw materials can be more evenly dissolved in the molten steel, making the distribution of various elements more uniform, greatly reducing the occurrence of component segregation.

[0087] Step S2, forging deformation, includes the following steps:

[0088] Step 1: The first stage of forging heating: the forging is heated with the furnace, the heating rate of the forging is ≤60℃ / h, the billet is heated to 550℃ and kept warm, the holding time of the forging is determined according to the thickness of the forging, specifically 2-2.5h / 100mm.

[0089] Step 2, the second stage of forging heating, the forging is heated with the furnace, the heating time of the forging is ≤60℃ / h, the billet is heated to 850℃ and kept warm, the holding time of the forging is determined according to the thickness of the forging, specifically 2-2.5h / 100mm.

[0090] Step 3, the third stage of forging heating, the forging is heated with the furnace, the heating time of the forging is ≤60℃ / h, the billet is heated to 1170℃ and kept warm, the holding time of the forging is determined according to the thickness of the forging, specifically 2.5-3h / 100mm.

[0091] Step 4, forging, forging blank size φ560mm*2300mm, upset to H=1500mm, flatten after upsetting, draw to 650mm*1500mm, return to the furnace for insulation>4h, the blank is taken out of the furnace and upset to a height of 550mm Vertically press the outer diameter to 700mm, turn 90° to press the outer diameter to 700mm, turn 90° to press the outer diameter to 500mm, and then upset to a height of 550mm, square and lengthen, finish forming, and lightly chamfer the edges and corners. After forging is completed, the forging is heated to 830℃ in the furnace, kept warm for 2 to 3 hours, and finally water-cooled.

[0092] Step S3, solid solution, includes the following steps:

[0093] Step 1: The first stage is solid solution. The forging temperature into the furnace is 240°C, the solid solution temperature of the forging is 880°C, the solid solution holding time of the forging is 3h, and then the forging is water-cooled to room temperature.

[0094] Step 2, the second stage of solid solution, the forging temperature into the furnace is 180℃, the solid solution temperature of the forging is 880℃, the solid solution holding time of the forging is 3h, and then the forging is water cooled to room temperature.

[0095] Step S4, aging, includes the following steps:

[0096] The forgings’ furnace entry temperature is 140°C, the forgings’ aging temperature is 510°C, the forgings’ aging holding time is 2h, and the forgings are air-cooled to room temperature after being taken out of the furnace.

[0097] Finally, the forgings are sampled and comprehensively tested. After the quality is qualified, the forgings are rough-turned and delivered.

[0098] Forging inspection:

[0099] Comprehensive mechanical testing:

[0100] The forgings were subjected to tensile tests and impact tests, and the results are shown in Table 2.

[0101]

[0102] Table 2

[0103] At ultra-low temperatures (-196°C), the three-dimensional impact energy of the material meets the standard requirements, indicating that the material still has good strength and toughness at ultra-low temperatures.

[0104] Non-metallic inclusion detection:

[0105] Detection method: Ⅲ6GOST1778-70.

[0106] Test results: Figure 5 shown.

[0107] Grain size detection:

[0108] Test method: ASTME112-2017.

[0109] Magnification: 100x.

[0110] Acceptance index: Grain size ≥ level 6.

[0111] Test results: Figure 6 As shown, the grain size is level 7.

[0112] Tissue testing:

[0113] Test method: GB / T13298-2015.

[0114] Magnification: 100x.

[0115] Acceptance criteria: Ferrite is not allowed.

[0116] Test results: Figure 7 As shown, the structure is martensite, and no ferrite is seen.

[0117] Embodiment 3:

[0118] A manufacturing process for ultra-low temperature XM16 precipitation type martensitic stainless steel, such as Figure 1 As shown, the following steps are included:

[0119] Step S1, raw material preparation:

[0120] The raw materials include elements counted by weight percentage, C 0.01%, Si 0.33%, Mn 0.35%, P 0.014%, S 0.003%, Cr 11.48%, Ni 9.36%, Mo 0.44%, Ti 1.19%, Cu 2.42%, Ta and Nb 0.25% in total, and the balance is iron.

[0121] Smelting method: vacuum smelting + vacuum consumables. During vacuum smelting and vacuum consumables, since the entire smelting process is carried out under vacuum or near-vacuum conditions, the contamination of molten steel by impurities such as air and oxygen is effectively avoided, and the formation of inclusions such as oxides and sulfides is reduced, thereby significantly improving the purity and organizational stability of the molten steel. In addition, the alloy raw materials can be more evenly dissolved in the molten steel, making the distribution of various elements more uniform, greatly reducing the occurrence of component segregation.

[0122] Step S2, forging deformation, includes the following steps:

[0123] Step 1: The first stage of forging heating: the forging is heated with the furnace, the heating rate of the forging is ≤60℃ / h, the billet is heated to 570℃ and kept warm, the holding time of the forging is determined according to the thickness of the forging, specifically 2-2.5h / 100mm.

[0124] Step 2, the second stage of forging heating, the forging is heated with the furnace, the heating time of the forging is ≤60℃ / h, the billet is heated to 870℃ and kept warm, the holding time of the forging is determined according to the thickness of the forging, specifically 2-2.5h / 100mm.

[0125] Step 3, the third stage of forging heating, the forging is heated with the furnace, the heating time of the forging is ≤60℃ / h, the billet is heated to 1180℃ and kept warm, the holding time of the forging is determined according to the thickness of the forging, specifically 2.5-3h / 100mm.

[0126] Step 4, forging, forging blank size φ560mm*2300mm, upset to H=1500mm, flatten after upsetting, draw to 650mm*1500mm, return to the furnace for insulation>4h, the blank is taken out of the furnace and upset to a height of 550mm Vertically press the outer diameter to 700mm, turn 90° to press the outer diameter to 700mm, turn 90° to press the outer diameter to 500mm, and then upset to a height of 550mm, square and lengthen, finish forming, and lightly chamfer the edges and corners. After forging is completed, the forging is heated to 830℃ in the furnace, kept warm for 2 to 3 hours, and finally water-cooled.

[0127] Step S3, solid solution, includes the following steps:

[0128] Step 1: The first stage is solid solution. The forging temperature into the furnace is 240°C, the solid solution temperature of the forging is 890°C, the solid solution holding time of the forging is 5h, and then the forging is water-cooled to room temperature.

[0129] Step 2, the second stage of solid solution, the forging furnace temperature is 180℃, the forging solid solution temperature is 890℃, the forging solid solution holding time is 5h, and then the forging is water cooled to room temperature.

[0130] Step S4, aging, includes the following steps:

[0131] The forgings’ entering furnace temperature is 140℃, the forgings’ aging temperature is 560℃, the forgings’ aging holding time is 3h, and the forgings are air-cooled to room temperature after being taken out of the furnace.

[0132] Finally, the forgings are sampled and comprehensively tested. After the quality is qualified, the forgings are rough-turned and delivered.

[0133] Forging inspection:

[0134] Comprehensive mechanical testing:

[0135] The forgings were subjected to tensile tests and impact tests, and the results are shown in Table 3.

[0136]

[0137] Table 3

[0138] At ultra-low temperatures (-196°C), the three-dimensional impact energy of the material meets the standard requirements, indicating that the material still has good strength and toughness at ultra-low temperatures.

[0139] Non-metallic inclusion detection:

[0140] Detection method: Ⅲ6GOST1778-70.

[0141] Test results: Figure 8 shown.

[0142] Grain size detection:

[0143] Test method: ASTME112-2017.

[0144] Magnification: 100x.

[0145] Acceptance index: Grain size ≥ level 6.

[0146] Test results: Fig. 9 As shown, the grain size is level 7.

[0147] Tissue testing:

[0148] Test method: GB / T13298-2015.

[0149] Magnification: 500x.

[0150] Acceptance criteria: Ferrite is not allowed.

[0151] Test results: Fig.10 As shown, the structure is martensite, and no ferrite is seen.

[0152] Forging performance test after solid solution:

[0153] Sampling size: 50mm*50mm*200.

[0154] 1. The yield strength curves of samples at different temperatures are shown in Table 1. The holding time is constant for 1 hour. Fig.11 shown.

[0155] 2. Keep the temperature constant at 880℃, and the yield strength curve of the sample at different times, such as Fig.12 shown.

[0156] Performance test of forgings after aging:

[0157] Sampling size: 50mm*50mm*200.

[0158] 1. Under different aging temperatures, the average impact energy curve of the sample at -196℃ is as follows: Fig.13 shown.

[0159] 2. The average impact energy curve of the sample at -196℃ under different holding times at 510℃ is as follows: Fig.14 shown.

[0160] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0161] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A manufacturing process of ultra-low temperature XM16 precipitation type martensitic stainless steel, characterized in that: The following steps are involved: Step S1, raw material preparation, XM16 precipitation type martensitic stainless steel includes the following components by weight percentage: C≤0.03%; Si≤0.50%; Mn≤0.50%; P≤0.015%; S≤0.015%; Ni: 8.0-9.5%, Cr: 11.5-12.5%, Cu: 2.0-2.5%, Ti: 1.0-1.4%, Mo: 0.15-0.50%; the balance is Fe; Step S2, forging deformation, includes the following steps: Step 1: First stage forging heating: the billet is heated to 550±20℃ and kept warm; Step 2: The second stage of forging heating: the billet is heated to 850±20℃ and kept warm; Step 3: The third stage of forging heating: the billet is heated to 1170±10℃ and kept warm; Step 4: Deformation: The final forging temperature of the forging is controlled at 830±15℃. After forging, the forging is cooled; Step S3, solid solution, includes the following steps: Step 1: first stage solid solution, the solid solution temperature range of the forging is 880±10℃, and then the forging is cooled; Step 2, second stage solid solution, the solid solution temperature range of the forging is 880±10℃, and then the forging is cooled; Step S4: Aging. The aging temperature of the forging is in the range of 460 to 560°C.

2. The manufacturing process of ultra-low temperature XM16 precipitation type martensitic stainless steel according to claim 1, characterized in that: In step 1 of step S2, the heating rate of the forging is ≤60°C / h, and the holding time of the forging is determined according to the thickness of the forging, specifically 2-2.5h / 100mm.

3. The manufacturing process of ultra-low temperature XM16 precipitation type martensitic stainless steel according to claim 2, characterized in that: In step 2 of step S2, the heating rate of the forging is ≤60°C / h, and the holding time of the forging is determined according to the thickness of the forging, specifically 2-2.5h / 100mm.

4. The manufacturing process of ultra-low temperature XM16 precipitation type martensitic stainless steel according to claim 3 is characterized in that: In step 3 of step S2, the heating rate of the forging is ≤60°C / h, and the holding time of the forging is determined according to the thickness of the forging, specifically 2.5-3h / 100mm.

5. The manufacturing process of ultra-low temperature XM16 precipitation type martensitic stainless steel according to claim 4, characterized in that: In step 4 of step S2, the forging is cooled by water.

6. The manufacturing process of ultra-low temperature XM16 precipitation type martensitic stainless steel according to claim 1, characterized in that: In step 1 of step S3, the temperature of the forging entering the furnace is less than or equal to 240° C., and the solution heat preservation time of the forging is 3 to 5 hours.

7. The manufacturing process of ultra-low temperature XM16 precipitation type martensitic stainless steel according to claim 6, characterized in that: In step 2 of step S3, the temperature of the forging entering the furnace is less than or equal to 240° C., and the solution heat preservation time of the forging is 3 to 5 hours.

8. The manufacturing process of ultra-low temperature XM16 precipitation type martensitic stainless steel according to claim 7, characterized in that: In step S3, the forging is water-cooled after the first stage of solid solution treatment is completed, and the forging is water-cooled after the second stage of solid solution treatment is completed.

9. The manufacturing process of ultra-low temperature XM16 precipitation type martensitic stainless steel according to claim 1, characterized in that: In step S4, the aging holding time of the forging is in the range of 2 to 3 hours.

10. The manufacturing process of ultra-low temperature XM16 precipitation type martensitic stainless steel according to claim 1, characterized in that: In step S4, the forging is air-cooled to room temperature after aging.